Удосконалення мережевого інвертора комбінованої системи електроживлення з поновлювальними джерелами енергії - Шавьолкін, Олександр Олексійович; Кожемякін, Сергій Михайлович (НТУ "ХПІ", 2016)
Розглянуто однофазний мостовий інвертор напруги в режимі джерела струму. Для однополярного формування напруги запропоновано рішення з дворівневим і трирівневим релейним регулятором струму при зниженні кількості і обмеженні частоти перемикань транзисторів. В автономному режимі завдання струму формується пропорційно-інтегральним регулятором напруги. При роботі на мережу інвертор підключається через реактор, в автономному режимі паралельно навантаженню підключається конденсатор. Виконано моделювання роботи з мережею і нелінійним навантаженням.

Considered a single-phase current controlled voltage source bridge inverter for the converter unit with renewable energy sources. In parallel work with AC network the inverter is provides a power factor equal to one, regardless of the type of load and the direction of energy transfer. In autonomous mode, when the AC network is disconnected, inverter provides the energy transfer to the load. Proposed solutions with using a two-level and three-level hysteresis current controller with adjustable setting trigger of controller. This allows for the formation of a unipolar voltage inverter and to reduce the number of switching of transistors with limiting the frequency switching. When operating on AC power inverter current reference is formed in accordance with the load current and the power that is generated from renewable sources. In the autonomous mode, the instantaneous value of the load voltage is formed by a proportional-integral voltage controller that generates a reference to the hysteresis current controller. The current regulator is provides to limit the inverter current for transient regimes. The inverter is connected to AC power and load through the reactor. In the autonomous mode, the capacitor is connected parallel to the load. The inverter control system, which implements the proposed solutions have been developed. Simulation has executed for a system which includes a source AC with active and inductive impedance of power line, inver ter with its control system and combined load. The load is an active-inductive, and includes a rectifier with an output capacitor filter. The simulation results confirm the effectiveness of solutions that are offered.
Improvement of main inverter of combined power system with renewable energy sources
Keywords: комбінована система електропостачання; поновлювані джерела енергії; інвертор напруги; режим джерела струму; релейний регулятор струму; трирівневий релейний регулятор; регулятор напруги; автономний режим; моделювання; combined system of power supply; renewable energy; current controlled voltage; hysteresis current controller; three-level hysteresis controller; voltage controller; autonomous mode; modeling